World religions and norms of war - Popovski, Vesselin; Reichberg, Gregory M.; Turner, Nicholas (United Nations University Press, 2009)
Over more than two millennia, the world's leading religious traditions have provided the guidance in questions of when war can be justified, and of what methods and targets are permissible in war. Linking deep historical analysis to contemporary issues, this volume provides insight to the understanding of the role and influence of religion in the state politics. The book examines the norms of war in Hinduism, in Theravada Buddhism, in Japanese religion, in Judaism, in Roman Catholic Christianity, in Eastern Orthodox Christianity, in Protestant Christianity, in Shia Islam and in Sunni Islam, and discusses norms of war in cross-religious perspective.--Publisher's description.